Carbon Emission Disclosure: Evidence from Manufacturing Company - Kelvin Yauri; Luky Patricia Widianingsih (Indonesian Journal of Sustainability Accounting and Management, 2023)
This study aims to examine variables that affect carbon emissions disclosure. The variables tested in this study include media exposure, environmental performance, leverage, and firm size. Carbon emission disclosure is measured using a checklist based on the information request sheet provided by the Carbon Disclosure Project (CDP). The research sample was 34 manufacturing companies listed on the IDX selected from 2016-2020. Data analysis used pooled least squares. The result of this study indicates that the variables of media exposure, environmental performance, and company size have a significant positive effect on carbon emissions disclosure. Meanwhile, leverage has a significant negative impact on carbon emissions disclosure. This study implies that manufacturing companies need to change the perception that disclosing carbon emissions will only increase costs because disclosing carbon emissions also benefits companies and other stakeholders. The value of the study confirms the “inside and outside” drivers that can contribute to changes and improvements in carbon emission disclosure performance.